FAKTOR DETERMINAN PENYEBAB NON PERFORMING FINANCING PADA BANK PEMBIAYAAN RAKYAT SYARIAH DI INDONESIA PERIODE 2008-2015 - Fary Adisetya Putra; Imron Mawardi (Universitas Airlangga, 2018)
The goal of this research is to determine the factors that caused the problematicfunding of Bank Pembiayaan Rakyat Syariah in Indonesia during the period of 2008-2015. The method of research used is the quantitative approach. The sample of the research is Bank Pembiayaan Rakyat Syariah which is taken every three months for each variable during the period of 2008-2015. The analysis technique used is multiple regression analysis and the result is Y = 5,076 – 0,743PDB + 0,018FDR + 0,047BOPO + 0,040Inflation + 0,024AverageFunding, with R2 registration 0,749 or 74,9%.The result of the partial test shows that economic growth has a significant effect. The result of the simultaneous test shows that the five variables have significant effects in the problematic funding of Bank Pembiayaan Rakyat Syariah in Indonesia. REFERENCESAndarini, Marisa Ayu. 2015. Pengaruh Transmisi Moneter Syariah: Sertifikat Bank Indonesia Syariah dan Pasar Uang Antar Bank Syariah terhadap Operasi Moneter Syariah Dalam Mempengaruhi Inflasi di Indonesia Pada Periode 2011-2015. Skripsi diterbitkan. Fakultas Ekonomi dan Bisnis Unoversitas Airlangga Surabaya.Ascarya. 2012. Transmission Channel and Effectiveness of Dual Monetary Policy in Indonesia. Buletin Ekonomi Moneter dan Perbankan, Vol. 14, No. 3.Baasir, F. 2003. Pembangunan dan Krisis. Jakarta : Pustaka Harapan.Bank Indonesia. 2003. Himpunan Fatwa Dewan Syariah Nasional. Kerjasama Dewan Syariah Nasional, Majelis Ulama Indonesia dan Bank Indonesia.Bofinger, P. 2001. Monetary Policy: Goals, Institutions, Strategies, and Instruments. Oxford University Press.Chapra, M. Umer: 1985, Towards a Just Monetary System. Leicester,UK: The Islamic Fondation.Enders, W. 1995. Applied Econometric Time Series. New York: John Wiley and Sons, Inc.Harris, Richard. 1995. Using Cointegration Analysis in Econometrics Modelling. London: Prentice Hall.McEarchern, William A. 2000. Ekonomi Makro, Jakarta : Salemba EmpatPratiwi, Ardianing. 2013. Determinan Inflasi di Indonesia : Analisa Jangka Panjang dan Pendek. Jurnal Ilmiah Fakultas Ekonomi dan Bisnis Universitas Brawijaya Malang.Rahardja, Pratama dan Mandala Manurung. 2001.Teori Ekonomi Makro: Suatu Pengantar. Lembaga Penerbit Fakultas Ekonomi UI. JakartaSamuelson,Paul A. dan William D. Nordhaus. 2004. Ilmu Makro Ekonomi. Terjemahan, Jakarta: Media Global Edukasi.Siddiqui, Shamin Ahmad. 2008. An Evaluation of Research on Monetary Policy and Stability of the Islamic Economic System. Paper 7th International Conference on Islamic Economics: 30 Years of Research in Islamic Economics, Jeddah: KAAU-IRTI, April.Sugiyono, 2011. Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta.Taylor,J.B. 1995. The Monetary Transmission Mechanism : An Empirical Framework. Journal of Economic Perspective, 9.Warjiyo, Perry. 2004. Mekanisme Transmisi Kebijakan Moneter di Indonesia. Buku Seri Kebanksentralan No.11. Pusat Pendidikan dan Studi Kebanksentralan, Bank Indonesia, Jakarta.Warjiyo, P dan J. Agung. 2002. Transmission Mechanism of Monetary Policy in Indonesia. Directorate of Economic Research and Monetary Policy. Bank Indonesia, Jakarta.Warjiyo, P, dan Solikin. 2003. Kebijakan moneter di Indonesia. PSSK BI. JakartaWidarjono, Agus.2007. Ekonometrika Teori dan Aplikasi. Ekonisia. Yogyakarta.http://bi.go.id (diakses 9 Agustus 2016)http://ekonomi.kabo.biz/2011/01/jumlah-uang-beredar-m2.html?m=1(diakses 14 November 2016)